ChemInform Abstract: Explaining Anomalies in Enamine Catalysis: "Downstream Species" as a New Paradigm for Stereocontrol. Issue 17 (April 2016) - Bures, Jordi; Armstrong, Alan; Blackmond, Donna G.
Abstract: Review: 25 refs.